(untitled) (Malaysian Journal of Civil Engineering, 2023)
Ready-mixed concrete (RMC) is a contemporary item that facilitate to mix concrete in a specialized yard and deliver it at site while ensuring the quality as fresh concrete. The transit time of RMC, which is influenced by road congestion, is important since it may have an impact on the workability and compressive strength of RMC. Therefore, it is necessary to investigate the impact of transit time on properties of RMC. In this study, a two-phased experimental program was designed; where RMC has been used with (phase-1) and without admixture (phase-2). Concrete mix-ratio was designed to attain M20 concrete; however, the target strength was 25MPa. Fresh concrete properties, i.e., workability, was measured at designated times (i.e., 0, 45, 90, 120, 150, 180 and 210minutes) over a period of 3.5 hours after the mixing of concrete. Over this period, concrete-mixer was continuously rotated at 18-20 rpm speed and cylinders were cast at previously mentioned time intervals. The experimental results showed that transit time has a remarkable impact on workability of RMC when the admixture is not utilized, i.e., slump value reduced from 210 to 25mm over 3.5 hrs. travelling. However, the slump value can be maintained up to 115mm using 1% admixture. In contrast, there is no remarkable impact of transit time on the compressive strength as the average strength in both phases reached or relatively close to the target strength (i.e., 25MPa). The target strength compliance might be attributed to the continuous rotation of the RMC mixer during the transit time